Credit Expansion, 1920 to 1929, and its Lessons - Persons, Charles E. (Quarterly Journal of Economics, 1930)
Credit Expansion. — Bank loans and investments, 95. — Urban real estate mortgages; held by banks, mortgage trusts, mutual savings banks, Life Insurance Companies, Building and Loan Associations, 96. — Farm mortgages; held by Federal Land banks, Joint Stock banks; general data, 105. — Securities outstanding, 107. — Installment selling; electrical equipment, radio industry, General Motors Acceptance Corporation, 108. — Summary, 115. — Credit expansion somewhat analogous to monetary inflation, 119. — Consequence of credit expansion: illustrated by developments in the radio industry, the automobile industry, the construction industry, 121. — Conclusion, 128.